(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The paper presents constructive solutions ofcomposite beams, shown the results of experimental research and defined features of their destruction of I- beams with web of oriented strand board. Keywords:wooden beam composite section, wooden frame, oriented strand board, glued constructions.